Observational case studies of treatment of skin disorders with natural phages in Ganga water - Bharat Jhunjhunwala; Rakesh Kumar Bhatnagar; Ashutosh Shukla; Sanjay Kumar; Amit Patel; Jyotsana Khattri; Amit Kundu; Madhvi Sanwelka (Our Dermatology Online, 2021)
Background: Skin conditions have multiple causes. Natural phages in the Ganga River have bactericidal qualities against a number of bacterial infections, which help resolve skin conditions. Materials and Methods: We collected water from upper reaches of the Ganga River where the number of isolates of phages was more than 200 according to a study of the National Environmental Engineering Institute, Nagpur. The water was collected in May 2020 before the onset of monsoons and stored with sediments so that the phages adsorbed in the sediments cleaned up the overlaying column of water of all coliforms. We supplied the water by post to a number of volunteers who took the water through oral, topical or nasal route as per their convenience. Thirty-nine of the 52 volunteers provided data by telephone on their skin conditions on which this study is based. Results: The results show that an improvement of 1.7 on Likert Scale of 1-10 is obtained on skin conditions as per assessment of the volunteers after a treatment of 100 days. Further improvement of 1.0 on Likert Scale was reported after 85 days of stoppage of treatment. Conclusions: Natural phages of Ganga river could provide an inexpensive treatment not only for skin conditions but other comorbidities as well because skin conditions have multiple causes and phages of Ganga water may work at multiple levels.